Louise Élisabeth of France, engraving - Anton Fritz (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Louise Élisabeth of France, engraving. Elisabeth, Prinzessin von Frankreich
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons; Iconographie